Thurston Island (West Antarctica) Between Gondwana Subduction and Continental Separation: A Multistage Evolution Revealed by Apatite Thermochronology. Issue 3 (7th March 2019) - Zundel, Maximilian; Spiegel, Cornelia; Mehling, André; Lisker, Frank; Hillenbrand, Claus‐Dieter; Monien, Patrick; Klügel, Andreas
Abstract: The first low‐temperature thermochronological data from Thurston Island, West Antarctica, provide insights into the poorly constrained thermotectonic evolution of the paleo‐Pacific margin of Gondwana since the Late Paleozoic. Here we present the first apatite fission track and apatite (U‐Th‐Sm)/He data from Carboniferous to mid‐Cretaceous (meta‐) igneous rocks from the Thurston Island area. Thermal history modeling of apatite fission track dates of 145–92 Ma and apatite (U‐Th‐Sm)/He dates of 112–71 Ma, in combination with kinematic indicators, geological information, and thermobarometrical measurements, indicate a complex thermal history with at least six episodes of cooling and reheating. Thermal history models are interpreted to reflect Late Paleozoic to Early Mesozoic tectonic uplift of pre‐Jurassic arc sequences, prior to the formation of an extensional Jurassic‐Early Cretaceous back‐arc basin up to 4.5 km deep, which was deepened during intrusion and rapid exhumation of rocks of the Late Jurassic granite suite. Overall Early to mid‐Cretaceous exhumation and basin inversion coincided with an episode of intensive magmatism and crustal thickening and was followed by exhumation during formation of the Zealandia‐West Antarctica rift and continental breakup. Final exhumation since the Oligocene was likely triggered by activity of the West Antarctic rift system and by glacial erosion. Key Points: First apatite fission track and apatite (U‐Th‐Sm)/He data of Thurston Island constrain thermal evolution since the Late Paleozoic Basin development occurred on Thurston Island during the Jurassic and Early Cretaceous Early to mid‐Cretaceous convergence on Thurston Island was replaced at 95 Ma by extension and continental breakup